Zambia : Sixth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Requests for Waiver of Nonobservance of Performance Criterion, and Financing Assurances Review: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Zambia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Zambia's strong economic performance continues under the Extended Credit Facility arrangement. With a broadly unchanged macroeconomic outlook, the medium-term policy stance remains appropriate, but vigilance is warranted. The strengthening economy provides an opportunity for more rapid poverty reduction and employment creation. The fiscal program remains appropriate. As the government moves to tap the sovereign bond market, it will be important to strengthen debt and liquidity management capacity. Reforming the pricing and marketing system for maize remains critical. Executive Directors support the Bank of Zambia (BoZ)'s monetary policy tightening.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet